1988
DOI: 10.1037/0022-0167.35.2.154
|View full text |Cite
|
Sign up to set email alerts
|

Relation of state and trait anxiety to different components of career indecision.

Abstract: Several studies have reported evidence that a substantial relation exists between career indecision and anxiety. However, little research has been reported that would explain the relation in empirical terms. This study was designed to determine if state and trait anxiety relate differentially to various components of career indecision. To accomplish this objective, we generated factor scores from the Career Decision Scale (CDS) and correlated them individually with the two measures of anxiety. The results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
59
0
8

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 27 publications
(41 reference statements)
8
59
0
8
Order By: Relevance
“…In addition, the evidence gathered with regard to indecision typology points toward chronically indecisive types having the highest levels of negative personality traits such as neuroticism, global instability and state anxiety (Tokar, Fischer, & Subich, 1998). Moreover, other studies have reported on the personality dimensions that tend to be associated with high levels of career indecision such as low extraversion (Newman, Gray & Fuqua, 1999), anxiety (Fuqua, Newman, & Seaworth, 1988), depression (Saunders, Peterson, Sampson, & Reardon, 2000) and fear of commitment (Leong & Chervinko, 1996).…”
mentioning
confidence: 99%
“…In addition, the evidence gathered with regard to indecision typology points toward chronically indecisive types having the highest levels of negative personality traits such as neuroticism, global instability and state anxiety (Tokar, Fischer, & Subich, 1998). Moreover, other studies have reported on the personality dimensions that tend to be associated with high levels of career indecision such as low extraversion (Newman, Gray & Fuqua, 1999), anxiety (Fuqua, Newman, & Seaworth, 1988), depression (Saunders, Peterson, Sampson, & Reardon, 2000) and fear of commitment (Leong & Chervinko, 1996).…”
mentioning
confidence: 99%
“…Literature review on anxiety in scope of career development process shows that studies particularly focus on the relation between career indecision and anxiety (Campagna, & Curtis, 2007;Daniels, Stewart, Stupnisky, Perry, & LoVerso, 2011;1988;Fuqua, Seaworth & Newman, 1987;Hawkins, Bradley & White, 1977;Peng, 2005).…”
Section: Sonuç Tartışma Ve öNerilermentioning
confidence: 99%
“…Literatürde kariyer gelişimi sürecinde kaygı ile ilişkili olarak yapılan çalışmalara bakıldığında, çalışmaların özellikle kariyer kararsızlığı (career indesicion) ve kaygı arasındaki ilişkiye odaklandığı görülmektedir (Campagna ve Curtis, 2007;Daniels, Stewart, Stupnisky, Perry ve LoVerso, 2011;Fuqua, Newman ve Seaworth;1988;Fuqua, Seaworth ve Newman, 1987;Hawkins, Bradley ve White, 1977;Peng, 2005). Örneğin; Mojgan, Kadir ve Soheil (2011), İranlı lisans öğrencileri ile yaptığı çalışmalarında sürekli kaygının kariyer kararsızlığında durumluk kaygıdan daha fazla etkiye sahip olduğunu, kaygı ve kariyer kararsızlığı arasındaki ilişkinin pozitif yönde olduğunu bulmuşlardır.…”
unclassified
“…Based on anxiety studies (Fuqua, Newman, & Seaworth, 1988;Spielberger, 2010), there are two types of anxiety: state anxiety as a transitory emotional state and trait anxiety as a stable individual difference in anxiety-proneness. Even though no implication of causality can be made, sate anxiety or the indecision, some college students are undecided because the process of making a decision arouses strong state anxiety.…”
Section: Introductionmentioning
confidence: 99%